Pelatihan Kader Dalam Upaya Pencegahan Stunting Di Desa Talang Curup - Lorenza, Gracelia Mona; Pramana, Cipta; Fadhilah, Siti (Universitas Dehasen Bengkulu, 2025)
Stunting in Indonesia is a health issue that continues to receive serious attention from the government. According to data from the Indonesian Nutritional Status Survey (SSGI), the prevalence of stunting in Indonesia has shown a significant downward trend in recent years. The most striking decline occurred between 2021 and 2022, when the prevalence of stunting dropped from 24.4% to 21.6% (Ministry of Health, 2023a). The 2024 Indonesian Health Survey showed that the prevalence of stunting in toddlers aged 0-59 months was 15.8%, while in children aged 0-23 months (toddlers) it was 12.9% (Ministry of Health, 2023b). The government aims to reduce the stunting rate to 14% by the end of 2024, requiring an average reduction of 1.8% to achieve this target (Teja, 2022). The objectives to be achieved through the activity